The Van Hoe Collection : grammar of textiles - Hoe, Rozemarijn van; Zurstrassen, Benjamin; Valcke, Johan; Verschuere, Klaus (Antwerpen : Hopper & Fuchs, 2020)
The Van Hoe Collection - Grammar of Textiles' shows a selection of approximately 80 studies and drawings from the late 19th century to the mid-20th century from the collection of designer, textiles and artist Marc Van Hoe. A small selection of the collection will be exhibited in Brussels (Horta Museum) and Riga (Lithuania) in 2020. 'With this collection I try to make it clear that these are not only designs for textiles, there is more to it: making connections developments in the field of art, culture and politics is logical and at least as important. My collection mainly wants to stimulate curiosity when (learning to) read images. Marc Van Hoe " ... The man, or rather the artist, behind this rich collection consisting of fragments, sketches, drawings, enlargements for fabrics and wallpaper, does not keep his collection under lock and key. Sometimes the drawings simply hang with magnets on the wall, without frame and without glass. Their skin comes into contact with the air and the light, they live. They are not arranged in drawers. Van Hoe enthusiastically lets them open, a term about which the dictionary says: open the chalice, because this collection enters the conversation. Marc Van Hoe, designer of motifs and fabrics, constantly enters into dialogue with the drawings he saved from certain death. Sometimes the collector also becomes a designer. And allows his designs to blossom. from the thistle to the dahlia Behind the collection, a garden in which motifs bloom luxuriantly, we find the artists and craftsmen with whom Marc Van Hoe talks. He stylises and draws plants for a long time there, but literally scans them in before editing them. From tracing to scanning, from pixel to pigment. Stylization is of no importance as long as passion is involved."
The Van Hoe Collection - Grammar of Textiles' toont een selectie van circa 80 studies en tekeningen van einde 19de eeuw tot midden 20ste eeuw uit de collectie van ontwerper, textilien en kunstenaar Marc Van Hoe. Een kleine selectie van de collectie wordt in 2020 tentoongesteld in Brussel (Horta Museum) en Riga (Litouwen). Met deze collectie probeer ik duidelijk te maken dat dit niet alleen ontwerpen zijn voor textiel, er is meer aan de hand: verbanden leggen naar ontwikkelingen op het gebied van kunst, cultuur, politiek is logisch en minstens even belangrijk. Mijn collectie wil vooral nieuwsgierigheid aanwakkeren bij het (leren) lezen van beeld. Marc Van Hoe" ... De man, of liever de kunstenaar, achter deze rijke collectie bestaande uit fragmenten, schetsen, tekeningen, uitvergrotingen voor stoffen en behangpapier, houdt zijn verzameling absoluut niet achter slot en grendel. Soms hangen de tekeningen gewoon met magneten aan de muur, zonder lijst en zonder glas. Hun huid komt in aanraking met de lucht en het licht, ze leven. Ze liggen niet geordend in laden. Enthousiast laat Van Hoe ze ontluiken, een term waarover het woordenboek zegt: de kelk openen, zich ontsluiten. Want deze collectie gaat het gesprek aan. Marc Van Hoe, ontwerper van motieven en stoffen, treedt voortdurend in dialoog met de tekeningen die hij van een gewisse dood redde. Soms wordt de verzamelaar ook ontwerper. En laat hij zijn ontwerpen ontluiken, van de distel tot de dahlia. Achter de collectie, een tuin waarin motieven weelderig bloeien, vinden we de kunstenaars en ambachtslieden met wie Marc Van Hoe in gesprek gaat. Hij stileert en tekent planten niet langer, maar scant ze letterlijk in vooraleer hij ze gaat bewerken. Van calqueren naar scannen, van pixel naar pigment. Stilering heeft geen belang, als er maar passie in het spel is."
With texts by Benjamin Zurstrassen, Mireille Houtzager, Johan Valcke, Klaus Verschuere, and others.
Issued with "Oase/Oasis", illustrated booklet published by Hopper & Fuchs (32 pages; 16 cm).
Text in English and Dutch; with preface also in French.
boek
Keywords: Hoe, Marc van